Teachers’ views on students’ multilingual resources - tracking the impact of curriculum reform - Alisaari, Jenni; Bergroth, Mari; Heikkola, Leena Maria (Informa UK Limited, 2026)
Background
In 2016, Finnish core curriculum was revised, and teachers are now required to implement multilingual pedagogies in their classrooms. Objectives This study aims to examine how the national curriculum reform may have influenced teachers’ views on the use of multilingual students’ first languages in the classroom.
Methods
The data consists of 1855 Finnish teachers’ responses in two surveys, which were gathered in 2016 and 2021. The data included responses to both Likert scale questions and an open-ended question.
Results
The results indicated a slight increase in the use of multilingual practices at school. However, approximately one-fifth of the respondents still held views that go against the national guidelines.
Conclusions
To conclude our results, it seems that the national policies have not yet been fully implemented at the grassroots level. This indicates that a curriculum change at a national level does not automatically result in changes in the classroom level instruction.